INTEGRATION OF LEAN WAREHOUSING AND LINE BALANCING APPROACHES IN OPTIMIZING LOGISTICS PERFORMANCE TO REDUCE WASTE AND INCREASE EFFICIENCY OF INBOUND-OUTBOUND COIL PROCESSES IN HRC WAREHOUSE SYSTEM - Pranaditya, Ghani Bayu; Immawan, Taufiq (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to optimize the performance of warehousing logistics in inbound and outbound HRC coil activities at PT. XYZ through the integration of Lean Warehousing and Line Balancing approaches. The main problems faced are distribution delays due to operational bottlenecks, imbalance in workload between processes, and the absence of an effective distribution flow management system. The methods used include observation, case studies, brainstorming, and the Root Cause Analysis (RCA) approach supported by Fishbone Diagrams, Pareto Charts, and 5 Whys analysis. The data analyzed includes total warehousing profits from January to October 2024, factors causing delays, and standard time measurements for each work activity. The RCA results identified six dominant factors contributing to 80.44% of delays. Based on these findings, a solution was designed using the 5W + 1H method, including a loading and unloading slot booking system, development of outbound coil buffer areas, standard time measurements, forklift preventive checklists, and line balancing of work activities. The design implementation increased inbound efficiency from 29% to 74% and outbound from 34% to 62%. Inbound idle time decreased from 14,059.21 seconds to 1,988.85 seconds (savings of 201 minutes), while outbound decreased from 15,504.01 seconds to 4,907.28 seconds (savings of 176 minutes). Inbound balance delay decreased from 71% to 26%, outbound from 66% to 38%, and the smoothing index showed a more even workload distribution. These findings prove that integrating Lean Warehousing and Line Balancing reduces waste, accelerates distribution flows, and increases HRC coil warehousing productivity.